Studies on the effect of plant and chemical antihelminthic drugs on Gyrodactylus derjavini (Mikailov, 1975), an ectoparasite of the young Caspian salmon (Salmo trutta caspius Kessler) in fish farms in Azerbaijan - Mikailov, T. K.; Ibrahimova, N. E.; Rzayev, F. H. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
The paper reports on the research, conducted in 2013, of the effects of plant and chemical drugs on Gyrodactylus derjavini (Mikailov, 1975), a pathogenic ectoparasite of the young Caspian salmon (Salmo trutta caspius Kessler) in the Chaykend salmon farm in Azerbaijan.